2008
DOI: 10.1677/jme-08-0102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic undernutrition and leptin on GOAT mRNA levels in rat stomach mucosa

Abstract: The most unique feature of ghrelin is the acyl-modification of a hydroxyl group of the Ser3 in the N-terminus. The Ser3 is commonly modified by n-octanoic acid in vertebrates being needed for its biological effects, at least in terms of feeding. Therefore, a critical question regarding the role of ghrelin was to characterize the mechanism involved in its acylation. The acyltransferase that catalyzes ghrelin octanoylation has been recently identified and named ghrelin O-acyltransferase (GOAT). The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 36 publications
7
79
2
3
Order By: Relevance
“…Curiously, Goat mRNA expression remained unaltered in fed and fasted rats. Only fasted rats treated with leptin showed an increase in Goat mRNA expression (61).…”
Section: Goat Mrna Expression and Its Regulationmentioning
confidence: 94%
See 2 more Smart Citations
“…Curiously, Goat mRNA expression remained unaltered in fed and fasted rats. Only fasted rats treated with leptin showed an increase in Goat mRNA expression (61).…”
Section: Goat Mrna Expression and Its Regulationmentioning
confidence: 94%
“…Moreover, the analysis of GOAT mRNA in samples enriched with mouse gastric ghrelin cells has demonstrated a high expression of GOAT within ghrelin cells and a high correlation with ghrelin distribution (60). GOAT mRNA expression was also evaluated in rat tissues which contained a similar pattern of expression observed in human and mouse tissues (61).…”
Section: Goat Mrna Expression and Its Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic undernutrition markedly increased the expression of GOAT mRNA levels in stomach mucosae, offer a mechanistic explanation of the increased acyl ghrelin levels observed in patients with severe malnutrition (Gonzá lez et al, 2008). Using absorbable medium-chain fatty acid, GOAT-ghrelin system could act as a nutrient sensor to tell the brain that high caloric food is available, leading to fat storage, nutrient partitioning, and growth signals (Kirchner et al, 2009).…”
Section: Normal Physiology Expression and Regulation Of Ghrelinmentioning
confidence: 99%
“…In rats, GOAT mRNA is also expressed in hypothalamus, stomach, intestine, ovary, serum, placenta, muscle, heart, and adrenal glands (Gonzalez et al, 2008). Gutierrez et al (Gutierrez et al, 2008) demonstrated that GOAT transcripts were most abundant in stomach and pancreas in humans.…”
Section: Expression and Distribution Of Goatmentioning
confidence: 99%